Alterations in Sensorimotor and Mesiotemporal Cortices and Diffuse White Matter Changes in Primary Progressive Multiple Sclerosis Detected by Adiabatic Relaxometry - Filip, Pavel; Dufek, Michal; Mangia, Silvia; Michaeli, Shalom; Bareš, Martin; Schwarz, Daniel; Rektor, Ivan; Vojtíšek, Lubomír (Frontiers in Neuroscience, 2021)
Background: The research of primary progressive multiple sclerosis (PPMS) has not been able to capitalize on recent progresses in advanced MRI protocols. Objective: The presented cross-sectional study evaluated the utility of four different MRI relaxation metrics and diffusion weighted imaging in PPMS. Methods: Conventional free precession T1 and T2, and rotating frame adiabatic T1ρ and T2ρ in combination with diffusion weighted parameters were acquired in 13 PPMS patients and 13 age and sex-matched controls. Results: T1ρ, a marker of crucial relevance for PPMS due to its sensitivity to neuronal loss, revealed large-scale changes in mesiotemporal structures, sensorimotor cortex and cingulate, in combination with diffuse alterations in the white matter and cerebellum. T2ρ, particularly sensitive to local tissue background gradients and thus indicator of iron accumulation, concurred with similar topography of damage, but of lower extent. Moreover, these adiabatic protocols outperformed both conventional T1 and T2 maps and diffusion tensor/kurtosis approaches –methods previously used in the MRI research of PPMS. Conclusion: This study introduces adiabatic T1ρ and T2ρ as elegant markers confirming large-scale cortical grey matter, cerebellar and white matter alterations in PPMS invisible to other in vivo biomarkers.